Determinant factors of entrepreneurship intentions of electronic technology education students in Nigerian universities - Ifeanyi Benedict Ohanu; Theresa Chinyere Ogbuanya (Journal of Global Entrepreneurship Research, 2018)
The major purpose of this study was to explore the determinant factors of entrepreneurship intentions of Electronic Technology Education students in Nigerian universities. The study explored the influence of entrepreneurial factors as well as entrepreneurial learning experiences activities on the entrepreneurial intentions of Electronic Technology Education students in the universities. The study adopted a correlational survey research design. The population for the study was 366 Electronic Technology Education undergraduate students. There was no sampling as a result of the manageable size of the population. The students were surveyed by direct contact using questionnaire. They were asked to indicate the entrepreneurship learning experiences activities they were participating in/would participate in as part of their curriculum. Data collected were analysed using descriptive statistics and multiple regressions. The findings show that the more entrepreneurial activities students are engaged in, the less the influence of entrepreneurial factors on their entrepreneurial intentions and this significantly increased entrepreneurial intentions of students who prefer career choice as an entrepreneur. The findings also revealed that there is a positive relationship between gender, age, career choice, parents' occupation, and entrepreneurial intentions of Electronic Technology Education undergraduate students. It was recommended that Electronic Technology Education undergraduate students should see career options with a balance view in order to understand their abilities before deciding to venture in any electronic business enterprise.
Keywords: 650; Electronic technology education; Entrepreneurship; Entrepreneurship intention; Perceived desirability; Subjective norm